CBMS-04 SIGNIFICANT ROLE OF HYPOXIA IN THE EXPRESSION AND FUNCTION OF OSTEOPONTIN IN CD44-HIGHLY EXPRESSED GLIOMA STEM-LIKE CELLS IN TUMOR PROGRESSION OF GLIOBLASTOMA. (16th December 2019) - Nishikawa, Masahiro; Inoue, Akihiro; Ohtsuka, Yoshihiro; Ozaki, Saya; Matsumoto, Shirabe; Suehiro, Satoshi; Yano, Hajime; Kanemura, Yonehiro; Tanaka, Junya; Ohnishi, Takanori; Kunieda, Takeharu
Abstract: The poor prognosis of glioblastoma multiforme (GBM) may be due to the surviving glioma stem-like cells (GSCs) in the tumor periphery after tumor resection. We demonstrated that CD44-expressed GSCs existed much more in the tumor periphery of high invasive (HI) type GBM than low invasive (LI) type GBM. The HI type was significantly associated with worse outcome, but how GSCs with high CD44 expression relate to tumor progression remains unknown. In this study, we investigated effects of hypoxia on CD44-directed signal pathways, leading to tumor invasion and proliferation in GBM. We focused on the CD44 ligand osteopontin (OPN) because it is known hypoxia affects the interaction of CD44 and OPN which promotes stemness and proliferation of cancer stem cells. We examined mRNA expressions of hypoxia inducible factor (HIF)-1a, HIF-2a, CD44 and OPN in tumor tissues of GBM and investigated effects of hypoxia (1%O2:severe or 5%O2:moderate) on the expression of these molecules using cultured GSCs that were established from tumor tissues showing high CD44 expression in the periphery of GBMs. In addition, we analyzed the effects of OPN on invasive, migratory and proliferative activities of GSCs under the hypoxic conditions. OPN was much higher expressed in the tumor periphery of LI type GBM than HI type GBM. Severe hypoxia significantly increased the expressions of HIF-1a and CD44 but did not OPN. On the other hands, moderate hypoxia promoted the expressions of HIF-2a and OPN. Knockdown of HIF-2a significantly inhibited OPN expression. In addition, the more OPN was expressed in the cultured GSCs under moderate hypoxia, the more the GSCs proliferated and decreased their invasive and migratory activities. In conclusion, GSCs existing in the tumor periphery of GBM can migrate or proliferate by changing CD44-directed signal pathways. Moderate hypoxia promoted HIF-2a/OPN/CD44 pathway, resulting in phenotypic transition to high proliferative tumors.